The impact of developing leadership capabilities in achieving organizational excellence – A field study on King Abdulaziz University employees – - Aljohani, Tareq Mohammed; Taibah, Hassan bin Abdul Qadir (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to study the impact of leadership development on achieving organizational excellence at King Abdulaziz University, knowing the reality of organizational excellence at the university from the point of view of the study sample, and investigating the reality of leadership capacity development at the university from the point of view of the study sample, and providing scientific recommendations based on the results. The study helps in knowing the effectiveness of leadership development programs and how they affect the achievement of organizational excellence. To achieve the objectives of the study, the researcher used the descriptive analytical approach, and data was collected by means of a questionnaire, and a simple random sample of (230) was taken from the study population, which numbered (537) leaders. Academic and administrative staff at King Abdulaziz University, and the data were treated statistically using the statistical package for social sciences program. The study reached many results, the most important of which is that there is interest and knowledge of the dimensions of organizational excellence within the university, and there is an application and interest in developing leadership human capabilities to a very high degree, while the development of intellectual capabilities leadership to a high degree, and this indicates the university’s interest in developing leadership capabilities in a way that achieves its goals, and that there is agreement from the majority of the study sample to know ways to solve the problems facing the administration, by relying on the various experiences and skills and benefiting from them in the decision-making process. Brainstorming, which helps in developing the intellectual leadership capabilities of leaders, and there is a need to provide employees with the scientific methods used at work, and to conduct workshops to develop their organizational capabilities, and it is necessary to enhance the benefit of proactive studies in the field of business, analyze strengths and weaknesses, and identify Opportunities, challenges and risks facing management, by knowing the appropriate analytical tools.
Keywords: organizational excellence; leadership capacity development; King Abdulaziz University